Analisa Penjualan Menggunakan Algoritma K-Means - Hadi, Febri; Diana, Yusvi; Meta, Monanda Rio (AI Society & STMIK Indonesia, 2022)
Garbage is leftover material that is no longer used from daily human activities. The Garbage Bank system is currently still manual in nature such as buying and selling waste from the Bengkalis community, waste price lists, types of waste and grouping waste categories. As a solution to these problems, the author builds a Software Design to digitize the previous system which was done manually. In this study the research methodology used is the Kanban method. In making this application the programming language used is PHP Framework Codeigniter, and MYSQL as a data storage area. With this application, it can help the Waste Bank to buy waste easily, safely and more efficiently.